A Study of Daily Variation in Physiological Oral Malodor - Hasegawa, Akira; Hori, Reiko; Imai, Rie; Ohmori, Misaki; Satoh, Shuichi (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 2000)
The objective of this study was to measure the daily variation in oral malodor in 30 healthy young adults using a portable sulphide monitor (Halimeter®Model RH-17, Interscan, U.S.A.) and organoleptic score 5 times a day-before breakfast, after breakfast, before lunch, after lunch, and before dinner. Whole saliva flow without stimulation, saliva pH, dental plaque, and tongue coating status were also assessed for 8 of the subjects. There was no significant difference observed in the Volatile SulphurCompounds (VSC) between males and females. The measured values of oral malodor were influenced by meal, with the highest values found before breakfast. There were significant differences between tongue coating status andVSC before breakfast. No significant correlation was observed among VSC, dental plaque, and amount of saliva in the resting period. Results suggest that daily variation in oral malodor in the subjectsmay be caused mainly by changes in tongue coating status. J. Jpn. Soc. Periodontol., 42 : 43-48, 2000.